Evaluating the functionality of rice bran wax oleogel in the formulation of a low saturated fatty acid shortcrust pastry - Trouchon, Adrien Louis Pascal (2018)
The initial objective of this study was to understand the properties and functionalities of rice bran wax (RBW) oleogels in rapeseed oil (RSO) at different RBW concentrations and controlled cooling rates. The second aim of the study was to investigate the potential application of RBW oleogel to partially replace shortenings and decrease saturated fatty acids (SAFA) concentration in shortcrust pastry (SCP) while maintaining a structure comparable to of a standard pastry. SCP were formulated with 0, 20, 40 and 83% SAFA reduction. Two different shortenings were tested for comparison: coconut oil (CNO) and palm oil (PO). With small and numerous crystals, RBW oleogels at 3 or 5% (w/w) and a fast cooling rate were firmer and had the ability to be self-standing for a longer time than when formed at a slow cooling rate or with low RBW concentration. When introduced in a 20% SAFA reduction SCP, the strongest oleogels had the ability to form a structured dough with the same firmness, viscosity and pastry hardness than a comparable industrial recipe. Although there were difficulties in preparing SCP with comparable shape, the final baked products were tested with three point bend tests and the results showed promising results at a 20% SAFA reduction. Further optimisations in the recipe could lead to an alternative to shortenings and saturated fatty acid sources in shortcrust pastry